Quantification of poor menstrual hygiene among women of reproductive age group in a slum of Kolkata - Dasgupta, Aparajita; Roy, Keya; Bandyopadhyay, Lina; Paul, Bobby (International Journal Of Community Medicine And Public Health, 2019)
Background: Menstruation, a phenomenon unique to the females, is the cyclical shedding of the inner lining of uterus. It is associated with myths and misconceptions and poor knowledge of the normal physiology. Above all, poor menstrual hygiene is a precursor of various morbidities related to the reproductive tract. This study was conducted among women of reproductive age (WRA) group with the aim to assess their socio demographic characteristics, to elicit the knowledge, attitude and practices regarding menstruation and to find the factors associated with the menstrual hygiene practice. Methods: This community based cross-sectional study was conducted among 152 women aged (15-49 years) during December 2017 to January 2018 in Lockgate area of Chetla, Kolkata, West Bengal, India. Data on socio-demographic characteristics, knowledge, attitude and practices towards menstruation were obtained from structured questionnaire. Outcome variable was menstrual hygiene practice. Descriptive statistics and logistic regression were performed to analyze the data by using SPSS 16.0 version. Results: The mean ages of the participants were 27±8 years. Inadequate knowledge, negative attitude and unsatisfactory practice towards menstruation were 73.7%, 65.1% and 62.5% respectively. Significant correlates were Lower level of education [AOR=1.6 (1.3, 2.1)] and less per capita income [AOR=4.7(1.4, 15.5)] for inadequate knowledge. Less per capita income [AOR=4.7(1.9, 11.1)] for negative attitude. Increasing age [AOR=1.1 (1, 1.2)] and lower level of education [AOR=1.3 (1.2, 1.6)] for unsatisfactory menstrual hygiene practice when adjusted with other variables in the multivariate analysis. Conclusions: Women need to be educated about the significance of menstruation, importance of high quality menstrual hygiene management, use of satisfactory absorbent material, proper and hygienic disposal of menstrual absorbent so as to enable them to lead a healthy reproductive life.